2008
DOI: 10.1093/rheumatology/ken386
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: the underlying cause of microvascular dysfunction in rheumatoid arthritis

Abstract: In this large cross-sectional study, we found for the first time systemic inflammation (CRP) to be independently associated with microvascular dysfunction in patients with RA. This strong correlation was independent of other conventional vascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 42 publications
4
49
1
3
Order By: Relevance
“…in a large, crosssectional study of 128 patients with ra, we reported that micro vascular endothelial dysfunction is directly correlated with CrP level and that this association is independent of other conventional vascular risk factors. 94 we have also reported that vascular function improves in patients who respond to therapy with anti-tnF agents or DmarDs, which suggests that, in the microcirculation at least, a reduction in inflammation, rather than choice of treatment per se, can be beneficial. 95 surrogate serological markers of cardiovascular risk such as coagulation abnormalities are more common or more pronounced in ra patients than in healthy controls, 96,97 as are markers of endothelial function or activation, or both.…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 73%
“…in a large, crosssectional study of 128 patients with ra, we reported that micro vascular endothelial dysfunction is directly correlated with CrP level and that this association is independent of other conventional vascular risk factors. 94 we have also reported that vascular function improves in patients who respond to therapy with anti-tnF agents or DmarDs, which suggests that, in the microcirculation at least, a reduction in inflammation, rather than choice of treatment per se, can be beneficial. 95 surrogate serological markers of cardiovascular risk such as coagulation abnormalities are more common or more pronounced in ra patients than in healthy controls, 96,97 as are markers of endothelial function or activation, or both.…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 73%
“…Some clinical studies relating to endothelial function testing have utilized the cutaneous microvasculature. It has been established that there are implications for microvascular function in a range of diseases including diabetes (Khan et al, 2000;Morris et al, 1995), rheumatoid arthritis (Galarraga et al, 2008) and in patients with cardiovascular risk factors (Huang et al, 2007;Ijzerman et al, 2003;Khan et al, 2003). Therefore, it may prove to be potentially very useful to be able to measure early microvascular dysfunction in animal studies of these diseases, and also in mouse models in which the genotype has been altered.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, better control of inflammation has been reported to lessen the risk of cardiovascular complications. 5,6 Subclinical process, however, may start quite early in disease, as studies show silently progressing micro vascular dysfunction in IMIDs correlating strongly with early inflammatory state. 7,8 Evaluation for early atherosclerosis, adoption of 'treat to target' concept for tight control of disease to bring down CRP or preferably high-sensitivity CRP (hs-CRP) level towards normal range are measures to keep CVS complications in abeyance in RA.…”
mentioning
confidence: 99%